Treatment of elephantiasis nostras verrucosa with CO2laser - Adrián De Quintana Sancho (Indian Dermatology Online Journal, 2019)
Elephantiasis nostras verrucosa (ENV) is the most severe form of chronic non-filarial lymphedema that leads to disfiguration of body parts. Multiple topical and surgical treatments have been typically used with high relapse rates and local complications. In this context, CO2 laser emerges as a new well-tolerated and effective treatment option. We report two cases of long-term evolution of elephantiasis nostras verrucosa recalcitrant to topical therapy and successfully treated with CO2 laser. Both of them were septuagenarians with personal history of obesity and suffered from lower extremities edema due to heart failure in one case, and due to chronic venous insufficiency in the other. We describe the procedure, the results and the advisable maintenance for preventing recurrence in this difficult to treat and chronic condition.